Micronutrient Deficiencies and the Human Gut Microbiota. Issue 8 (August 2017) - Mach, Núria; Clark, Allison
Abstract : Little is known about how micronutrient deficiencies affect the human gut microbiota. A study by Hibberd et al. illustrates how these deficiencies affect the composition and function of gut microbiota, and further, how different species realize changes in gene expression and cellular metabolism to cope with micronutrient shortages.